Synthesis of pyridine-free xylan sulfates. (15th February 2019) - Pfeifer, Annett; Heinze, Thomas
Highlights: Xylan sulfate is an important bioactive polysaccharide derivative. Binding of pyridine in xylan sulfate could be clarified. Pyridine is covalently bound to the reducing end group. The synthesis approach discussed allows the preparation of pure xylan sulfate. The structures could be evaluated by NMR spectroscopy. Abstract: The usual sulfation of polysaccharides applying chlorosulfuric acid and pyridine may form products containing pyridine-based impurities, which may yield toxic side effects. The synthesis of pyridine-free polysaccharide sulfates could be realized simply by using xylan that was treated with a reducing agent (NaBH4 ) prior to the sulfation reaction. The reduced xylan possess same reactivity compared to untreated xylan. The purity of the alternatively synthesized xylan sulfate is proofed by NMR spectroscopic studies. Thus, the simple reduction of the reducing end groups of the polysaccharide prior the sulfation is an efficient tool to get pure products, which may be scaled up easily.